Pengaruh Kecerdasan Emosional Terhadap Tingkat Pemahaman Akuntansi Pada Mahasiswa Akuntansi di Universitas Teknologi Digital - Dira Danira Akkrani; O. Feriyanto (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the effect of emotional intelligence on the level of accounting understanding in final year students of the Accounting Study Program at the Digital Technology University. This study uses a quantitative approach, data were collected through questionnaires from 90 respondents and analyzed by simple linear regression using SPSS. The results show that emotional intelligence has a positive and significant effect on accounting understanding as seen from the regression equation Y = 5703 + 1.233X and with a total effect of R² = 49% on accounting understanding as seen from the coefficient of determination. Intention, curiosity and relatedness are the most influential indicators, while communication skills have the lowest influence. The implications of the study emphasize the importance of strengthening emotional intelligence through interactive learning methods and communication skills training for students.